2007
DOI: 10.1371/journal.pmed.0040217
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Avoidable Blindness in Western Rwanda: Blindness in a Postconflict Setting

Abstract: BackgroundThe World Health Organization estimates that there were 37 million blind people in 2002 and that the prevalence of blindness was 9% among adults in Africa aged 50 years or older. Recent surveys indicate that this figure may be overestimated, while a survey from southern Sudan suggested that postconflict areas are particularly vulnerable to blindness. The aim of this study was to conduct a Rapid Assessment for Avoidable Blindness to estimate the magnitude and causes of visual impairment in people aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 15 publications
(20 reference statements)
8
77
10
Order By: Relevance
“…Observing data from other Brazilian regions and developing countries, the prevalence of blindness from cataract in the general population is much higher than what was seen here, with 1.49% in the metropolitan region of São Paulo (10) , 2.11% in a Brazilian indigenous group from Amazonia (11) , 2.61% of the whole population in Cambodia (2) ; 4.26% in Nigeria (12) ; 1.17% of the over 50 population in Ruanda and Kenya (13) ; and 2.01% of over 50's in Paraguay (14) . Compared to other Latin American countries, our data is similar to the metropolitan area of Buenos Aires that has 0.5% of bilateral blindness caused by cataract (15) .…”
Section: Discussioncontrasting
confidence: 60%
“…Observing data from other Brazilian regions and developing countries, the prevalence of blindness from cataract in the general population is much higher than what was seen here, with 1.49% in the metropolitan region of São Paulo (10) , 2.11% in a Brazilian indigenous group from Amazonia (11) , 2.61% of the whole population in Cambodia (2) ; 4.26% in Nigeria (12) ; 1.17% of the over 50 population in Ruanda and Kenya (13) ; and 2.01% of over 50's in Paraguay (14) . Compared to other Latin American countries, our data is similar to the metropolitan area of Buenos Aires that has 0.5% of bilateral blindness caused by cataract (15) .…”
Section: Discussioncontrasting
confidence: 60%
“…Considering studies published in the last 10 years, blindness prevalence in vulnerable groups vary from 1.1% in rural provinces from Burundi (Central Africa) to 8.1% in rural villages from Myanmar (South Asia). [12][13][14][15][16][17] Reasons for this wide variation may include sampling variations, age groups evaluated, availability of eye care services, genetic background of populations, and other specific environmental or regional causes.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Interestingly, there is no common simple pattern to describe vision conditions found in these different populations. Visual impairment, for instance, may be among highest rates in the world -as in rural villages from Myanmar [12] or close to the lower rates from middleincome countries -as in Rwanda [13] and Burundi [16]. Therefore, minorities and unprivileged populations should not be considered a homogeneous group and the comprehensive evaluation of each case may be a key step toward fulfilling the goals of universal eye care.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,[8][9][10]14,15 In contrast, Powe and colleagues found that 89.7% of all eyes with cataract operated in the United States mostly during the 1980s-when conventional extracapsular surgery predominated-achieved visual acuity of 20/40 or better. 16 While developing country cases with advanced cataracts and possibly neglected co-morbidities likely are fundamentally more difficult and less likely to lead to good outcomes than US cases were in the 1980s, and the method of ascertaining visual outcome is non-identical, there appears to be a large quality gap.…”
Section: John H Kempenmentioning
confidence: 97%
“…At the most straightforward level, the results show us that blindness remains a major problem in Eritrea, and that diseases such as cataract and glaucoma which require ophthalmic care are an important cause of blindness, as in several other surveys from Africa and elsewhere in the world. [5][6][7][8][9][10][11][12][13][14][15] While more than half of severe visual loss or blindness was attributed to cataract, only about 1% was attributed to surgical complications. However, in reading further (as noted by the authors), we find that blindness due to complications of cataract surgery must be one of the leading causes of blindness in single eyes, because 182 eyes (39.2% of those operated) present with visual acuity worse than 6/60.…”
Section: John H Kempenmentioning
confidence: 99%